Comportamento do Bitcoin em relação ao ouro e ao índice Nasdaq: Uma análise entre 2015 e 2024 - Balsan, Enrico Fernandes (Universidade Federal de São Carlos, 2025)
Since Bitcoin's emergence in 2008, its trajectory has been marked by a rapid rise, capturing the attention of investors, technology enthusiasts and even skeptics. While some see Bitcoin as a modern store of value, capable of protecting against inflation and economic uncertainties, others see it as a revolutionary asset, full of potential to generate significant returns in the short and medium term. But after all, does Bitcoin behave like a "digital gold" or like a high-risk asset, highly sensitive to fluctuations in the technology market? This study seeks to analyze this duality, investigating whether Bitcoin, despite its initial proposal of being a scarce and decentralized currency, is more similar to a safe asset, such as gold, or a volatile asset, such as the technology stocks on the Nasdaq index. For this, the period from January 2015 to January 2024 was considered, which includes moments of stability as well as turbulent scenarios, such as the Covid-19 pandemic and its global developments. Through a combination of literature review, descriptive statistics, time series decomposition and stationarity tests, the study revealed that Bitcoin, although it was conceived as a currency with store of value characteristics, presents a behavior more aligned with that of a high-risk asset. Its volatility exceeds even that of the Nasdaq index, consolidating its image as a disruptive but also unpredictable asset.
Bitcoin's Behavior Against Gold and the Nasdaq Index: An analysis between 2015 and 2024
Keywords: Criptomoedas; Ativo; Reserva de valor; Cryptocurrencies; Asset; Store of value; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA MONETARIA E FISCAL::INSTITUICOES MONETARIAS E FINANCEIRAS DO BRASIL